The inhibitory effects of Xiao-Gao-Jiang-Zhuo-containing serum on adipogenesis in 3T3-L1 preadipocytes - Chen, Liang; Han, Yu; Li, Jing; Feng, Chunpeng; Chen, Chen; Ye, Ting (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
BACKGROUND: Obesity and related metabolic diseases are becoming a worldwide epidemic, leading to increased mortality and heavy medical costs. Our Chinese herbal formula Xiao-Gao-Jiang-Zhuo (XGJZ) has remarkable effects on curing obese patients in the clinic, but the cellular and molecular basis remains unknown. This study aimed to reveal the molecular mechanism involved in adipogenesis in vitro. METHODS: Chinese herbal formula XGJZ-containing serum was prepared from XGJZ-treated obesity model rats. The function of XGJZ-containing serum was validated in 3T3-L1 preadipocytes. Oil O staining was performed to determine intracellular lipid accumulation in differentiated 3T3-L1 cells. The expression of pro-adipogenic transcription factors was measured to further validate the adipogenesis of 3T3-L1 adipocytes. The contents of triglyceride (TG), free fatty acid (FFA), and glycerin, along with the activities of lipid metabolism-related enzymes (including FAT, FATP1, DGAT, GPAT, ATGL, and HSL) were measured to study the lipogenesis in 3T3-L1 adipocytes. RESULTS: XGJZ-containing serum inhibited 3T3-L1 differentiation, decreased intracellular lipid accumulation, and suppressed the expression of pro-adipogenic transcription factors in differentiated 3T3-L1 cells. The contents of TG, FFA, and glycerin were decreased when treated with XGJZ-containing serum, which also modulated lipid metabolism-related enzyme activities. The activities of fatty acid transporters (FAT, FATP1) and lipid mobilization enzymes (ATGL, HSL) were promoted, while activities of triglyceride biosynthesis enzymes (DGAT, GPAT) were attenuated in differentiated 3T3-L1 cells. CONCLUSION: XGJZ-containing serum has inhibitory effects on adipogenesis in 3T3-L1 preadipocytes, affirming the effect of XGJZ in treating obesity. It provides evidence for the mechanism of obesity.
Keywords: adipogeneze; obezita; Glycerol; Triglycerides; Humans; glycerol; Transcription Factors; 3T3-L1 Cells; Adipogenesis; krysa rodu Rattus; lidé; zvířata; myši; Mice; buňky 3T3-L1; triglyceridy; Rats; PPAR gama; Obesity; transkripční faktory; Animals; PPAR gamma